Honfoglalás kori csontváz Békésszentandrás területéről - Marcsik Antónia; Kujáni Yvett (2020)
The archaeological site named as Békésszentandrás–Homok-hát-dűlő (M44 Motorway) was excavated in 2017, at that same site a human skeleton was unearthed and dated to the Hungarian Conquest period. The deceased was provided with a saber, an iron knife as grave goods, and his horse in the form of a so-called partial horse burial. The paper presents the results of the anthropological analysis of the human remains. The morphologic image of the specimen is Europid-Mongolid (Mongolid). On the top of the skull three different symbolic (incomplete) trepanations have been observed.
Keywords: Bölcsészettudományok; Történettudomány és régészet